Povezava modela podnebnih sprememb z modelom toplotnega odziva stavb - primer Slovenije - Vidrih, Boris (Strojniški vestnik, 2006)
The world's leading climatologists believe that global climate changes are inevitable. The basis for this is the fact that we are already facing climate changes that will become even more significant in the future. The impact of climate changes is and will be noticeable in all fields of human activity; therefore, it will also influence the supply and demand of energy. Since we are observing a longer period of time, comparable to the lifespan of a building, and the amount of energy demanded is an important factor, it is necessary to adjust the building and the renovation of buildings to the predicted climate changes. The prediction of a building's thermal response is the basis for the integral planning of the building and building services installation with which we create suitable living conditions. In order to predict the expected changes in the building's thermal response in the future it is necessary to correct the available meteorological variable databases today. In this paper we present various climate-change scenaria expected for Slovenia and the methods for correcting the starting points of the local meteorological databases. For the correction we used simplified mathematical models with which we - by forming test reference years (TRYs) - elaborate corrected test reference years (CTRYs). The latter are used for declaring the changes in energy demand in buildings and the effectiveness of a chosen building services installation that uses natural energy sources. As regards the predicted climate scenaria for the continental part of Slovenia, the energy use for heating buildings will be reduced by 1.5% to 31.4%. These climate changes will have a substantial influence on the thermal comfort in buildings during the summer. In the heavyweight and naturally ventilated residential buildings that are currently thermally comfortable, suitable summer temperatures will be exceeded during 20% to 33% of the summer. The effectiveness of natural and passive cooling techniques will radically change.In cooled buildings we can expect a 2-to-40-fold increase in the use offinal (end-use) cooling energy when compared to today. The results presentedin this paper confirm the fact that it is necessary to evaluate the consequences of global climate changes also from the point of view of energy use in buildings, their construction and building services installations.
Keywords: podnebne spremembe; modeliranje numerično; toplotni odzivi stavb; raba energije; Slovenia; Slovenija; zgradbe; toplotna izolacija